Minimum Instream Environmental Flow in Shatt Al-Hillah River (Journal of Engineering, 2023)
To maintain river flows necessary to meet social and ecological objectives, instream environmental flows are frequently used as a strategy. The capability of three alternative historical flow approaches to protect against low flows is shown in this study using gage stations in the Shatt Al-Hillah River in Iraq. The extension of the Shatt al-Hillah River is the focus of this research discussion on environmental flow assessment. The available data on discharge in this research were adopted for ten years from 2012-2021. Different flow methods were adopted to establish a minimum environmental flow in the Shatt Al-Hillah River. Three hydrological-based approaches: Tennant, modified Tennant, and low-flow metrics like 7Q10, were used to compare the results of the methods with the provision of a minimal environmental flow. The Tennant method relies on 30 % of the annual discharge rate as the minimum environmental instream flow. The modified Tennant method is based on 30% of the monthly average discharge rate as a minimum environmental instream flow. The 7Q10 method is based on the lowest daily discharge rate in 7 consecutive days for ten years. The results showed that the minimum instream environmental flow given by the Tennant method is 42.26 m3/s while the lowest value of the minimum instream environmental flow obtained from modified Tennant was 37.2 m3/s in January, and the largest value was 47.22 m3/s in August. The one obtained by the 7Q10 method was 50 m3/s in this research.